The chronology of human and animal presence in the decorated and sepulchral cave of Cussac (France). (8th March 2017) - Jaubert, Jacques; Genty, Dominique; Valladas, Hélène; Camus, Hubert; Courtaud, Patrice; Ferrier, Catherine; Feruglio, Valérie; Fourment, Nathalie; Konik, Stéphane; Villotte, Sébastien; Bourdier, Camille; Costamagno, Sandrine; et al.
Abstract: In this article, we present a first synthesis of the chronology of Cussac Cave (Dordogne, SW France). This deep cavern (1.6 km), discovered in 2000, is very well preserved ( e . g . intact floors) and thus favorable to research, especially given its rare association of parietal art and human remains, deposited in at least three locations. The scientific team working since 2009 presents here a first diachronic reconstruction of the natural (geological, biological) and anthropogenic (cultural, spiritual) elements relevant to the sectors of the cave accessible for study. In addition to the nuclear dating methods commonly used in karst contexts and decorated sites (U–Th and 14 C for speleothems, 14 C-AMS for organic materials, bone and charcoal), we drew upon other disciplines to determine the relative chronology of the events that occurred in the cave: geosciences (karstology, sedimentary geology, geoarchaeology), biological anthropology, paleontology, zooarchaeology, anthracology, ichnology, lithic and osseous technology, and of course, the study of parietal art. Their integrated study enabled us to define a coherent and global chronological framework. The results confirm that bears frequented the cavity several times before any human incursions. Humans later ventured into the cave after it had already undergone several phases of karstogenesis, collapse, sedimentation, erosion and concretion formation. The nuclear methods and relative dating methods employed concur in favor of the hypothesis of human incursions only during the Middle Gravettian period, approximately 28–29, 000 cal BP, to carry out spiritual, graphic and sepulchral activities. After the cave was abandoned by Gravettian people, some final sedimentary and biological events occurred (partial flooding, concretion formation, presence of mesofauna and microfauna, etc.), but were insufficient to significantly modify the decorated and sepulchral sanctuary. Later human frequentations (Late Glacial, Late Magdalenian, Late Neolithic) are quantitatively anecdotal and, most importantly, were limited to the cave porch and vestibular areas, which were sealed-off from the internal zone by rockfall debris and Late Glacial or Holocene concretion formations.